Infrared measurements in the spring 1987 ozone hole - Keys, J. G.; Goldman, Aaron; Matthews, W. A.; Murcray, F. J.; Murcray, D. G. (1988)
Solar spectra were recorded from Arrival Heights (McMurdo), Antartica, with a FTIR system during the austral spring of 1987. Spectra were recorded on 22 days from September 13 through October 28. The instrument was setup with 2 detectors for simultaneous operation in 2 wavelength regions. Several stratospheric gases have measurable absorptions in these regions including HCl, HNO3, O3, ClONO2, and NO2. The system is equipped with an automatic solar tracking system and records data on tape cartridges. A portable personal computer allows Fourier transforming and initial processing of some of the data. The HNO3 gas column amount shows large variations, but no apparent correlation with stratospheric temperature. The HCl column shows a steady increase from 0.9 x 10 to the 15th power molecules/sq.cm. on September 13 to 1.5 x 10 to the 15th power on October 6. McMurdo moved out of the polar vortex for a few days, and the HCl column jumped to 2.9 x 10 to the 15th power by October 11. Although McMurdo moved back under the vortex, the HCl continued to increase, reaching 3.4 x 10 to the 15th power at the end of the period.